2023
DOI: 10.1111/geb.13704
|View full text |Cite
|
Sign up to set email alerts
|

Global arbuscular mycorrhizal fungal diversity and abundance decreases with soil available phosphorus

Abstract: Aim Arbuscular mycorrhizal fungi (AMF) are widely distributed soil organisms that play critical roles in ecosystem functions. However, little is known about their global distribution and the underlying mechanisms. Here, we aimed to explore distribution pattern and key predictors of AMF diversity and abundance at the global scale. Location Global. Time Period 1987–2022. Major Taxa Studied Arbuscular mycorrhizal fungi. Methods We investigated the distribution pattern and key predictors of AMF diversity and abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 111 publications
3
6
1
Order By: Relevance
“…The AM fungal colonization rates in the inoculated plants ranged from 52 to 66% (Figure S5), suggesting successful fungal colonization according to a previous study summarizing global data . Limited colonization rates were detected in the uninoculated plants (Figure S5).…”
Section: Resultssupporting
confidence: 91%
“…The AM fungal colonization rates in the inoculated plants ranged from 52 to 66% (Figure S5), suggesting successful fungal colonization according to a previous study summarizing global data . Limited colonization rates were detected in the uninoculated plants (Figure S5).…”
Section: Resultssupporting
confidence: 91%
“…Surprisingly, however, a one-way ANOVA of the mean diversity indices reveals no significant difference in the diversity of AMF among the different points with different vegetation. Previous reports by Davison et al (2015), Xu et al (2017), andMa et al (2023) even showed that grasslands tend to have a higher AMF abundance and diversity, in contrast with the results of this study. According to Solís-Rodríguez et al (2020), aside from vegetation, abiotic factors, such as the chemical properties of the soil at the time the samples were collected, also have a significant role in structuring AMF communities.…”
Section: Association Of Amf and The Local Vegetation In The Trailcontrasting
confidence: 99%
“…This finding corroborates the presumed positive correlation between AMF and plant diversity (Hiiesalu et al 2014;Xu et al 2016). The plant diversity hypothesis suggests that as the diversity of plants in an ecosystem increases, more soil microbial niches emerge, which increases the likelihood for soil microorganisms, such as AMF, to find a viable plant host (Ma et al 2023). Similarly, the greater the diversity of AMF abundance and diversity, the more improved the ability of plants to absorb nutrients.…”
Section: Association Of Amf and The Local Vegetation In The Trailsupporting
confidence: 77%
“…Traditionally, it is believed that forests are more diverse than grasslands; nevertheless, new findings showed that grasslands present high microbial diversity. Among these microbial communities, AMF diversity is higher in grasslands globally [140]. In general, AMF diversity was not significantly different between South American grasslands and pastures.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, a new gap comes out in the information on the diversity of AMF at the level of ecosystem functioning that needs to be explored and investigated to contribute to the knowledge of these fungi and their interactions with their hosts in grasslands and pastures. It is important to highlight that the grassy ecosystems in general are named "grasslands" in sensu lato [140], without discriminating between pastures (grazed ecosystems with anthropogenic intervention, e.g., sowing of exotic species, thinning of shrubs, etc.) or grasslands sensu stricto (natural grasslands) as they were defined in this work.…”
Section: Discussionmentioning
confidence: 99%